Effects of Covid -19 Pandemic on Tourism in Kashmir - SHOWKAT AHMAD DAR; NASEER AHMAD LONE (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Tourism is defined as leisure travel. Tourism generates jobs and promotes long-term growth, benefiting local economies. The Mughal emperor Jahangir called it "paradise on Earth." Snow-capped mountains, enchanting gardens, majestic waterfalls, apple orchards, deep gorges, and poplar, deodar, and Chinar trees are among J&K's top attractions. Tourism is big business in J&K. Tourism, the country's largest service industry, boosts the state's GDP, foreign exchange, employment, and tax revenue. Jammu and Kashmir is a popular tourist destination due to its successful development. The Covid-19 outbreak hit Kashmir just as tourist season was starting, dampening spirits. Travel and tourism have spread a novel corona virus that is highly contagious. This jeopardizes the industry's future. This paper examines how the COVID-19 lockdown has affected the tourism industry and other activities. COVID-19 is expected to have significant effects on Kashmir tourism through 2020, resulting in reduced visitor numbers and travel restrictions. That the pandemic had severe consequences for the economic development of Kashmir Valley, located in the Indian state of Kashmir. Poorer people (tourist stakeholders) were also severely harmed, the findings show. COVID-19 pandemic early effects on tourism and cost.